Sleep paralysis : night-mares, nocebos, and the mind-body connection - Adler, Shelley R., 1963- (Studies in medical anthropology., 2011)
Sleep Paralysis explores a form of nocturnal fright: the "night-mare," or incubus. In its original meaning a night-mare was the nocturnal visit of an evil being that threatened to press the life out of its victim. Today, it is known as sleep paralysis-a state of consciousness between sleep and wakefulness, when you are unable to move or speak and may experience vivid and often frightening hallucinations. Culture, history, and biology intersect to produce this terrifying sleep phenomenon that is rarely recognized or understood in the contemporary United States